Analytical investigation of profile shifts on the mesh stiffness and dynamic characteristics of spur gears. (January 2022) - Wang, Jinhai; Yang, Jianwei; Lin, Yunlei; He, Yuping
Highlights: The analytical models of TVMS for profile-shifted spur gears are established. The positive shift decreases the TVMS so that it causes stronger vibrations in the gear system. The negative shift increases the TVMS so that it weakens vibrations in the gear system. The positive compound shift decreases TVMS and increases the vibration. The negative compound shift leads to TVMS rising and significantly reducing vibration. Abstract: Nowadays, profile shift is one of the most powerful techniques to achieve high-performance spur gear transmission system. Although this technique has been widely used in industry, its influence on time-varying meshing stiffness (TVMS) and dynamic characteristics is still unclear. This paper presents a novel analytical model of TVMS for profile-shifted spur gears. The modification coefficient and transition curve revise the proposed model. Afterward, numerical simulations are carried out to analyze individual and compound shifts based on a six-degree of freedom gear model. For individual shifts, the positive shift can decrease the gear tooth's stiffness and TVMS so that it causes stronger vibrations in the gear system. On the contrary, the negative shift can improve the gear tooth's stiffness and TVMS, thereby mitigating the gear system's vibration. For compound shift, S0 -gearing poses a slight impact on TVMS, but an unneglectable effect on dynamic characteristics. Besides, the S-gearing with the positive compound shift can decrease TVMS and increase vibration. In contrast, the S-gearing with the negative compound shift leads to TVMS rising and significantly reducing vibration. The insightful findings derived from the study can help engineers and manufacturers better understand the operation performance and dynamic features of profile-shifted spur gears.